A Review of Methodologies for the Detection, Quantitation, and Localization of Free Cysteine in Recombinant Proteins: A Focus on Therapeutic Monoclonal Antibodies - Metcalfe, Clive (Frontiers in Molecular Biosciences, 2022)
Free-cysteine residues in recombinant biotherapeutics such as monoclonal antibodies can arise from incorrect cellular processing of disulfide bonds during synthesis or by reduction of disulfide bonds during the harvest and purification stage of manufacture. Free cysteines can effect potency, induce aggregation, and decrease the stability of therapeutic proteins and the levels and positions of free cysteine in proteins is closely monitored by both manufacturers and regulators to ensure safety and efficacy. This review summarises the latest methodologies for detection and quantification of free cysteines